Aplicaciones del RFC 5213 – Proxy Mobile IPv6 – Comparación de ambientes móviles en redes académicas - Taffernaberry, Juan Carlos (2015)
The use of academic networks is producing important changes in research and education fields, providing new tools that bring us closer to other scientific and educational worldwide communities. Thus, investigations can be carried out between geographically dispersed work teams. A good complement for these scenarios is the use of mobility techniques. In this paper, a comparison between two different mobile IP alternatives is presented. Evaluated standards are Mobile IPv6 (MIPv6) and Proxy Mobile IPv6 (PMIPv6). Performance, advantages, disadvantages, configuration and installation comparisons are made. Afterwards the behavior of handover is evaluated for traditional and real time applications. Finally, comparisons and a conclusion are made.